Effects of Integrated Pest Management on Pest Damage and Yield Components in a Rice Agro-Ecosystem in the Barisal Region of Bangladesh - Alam, Mohammad Zahangeer; Crump, Alex R.; Haque, Md. Manjurul; Islam, Md. Sirajul; Hossain, Emran; Hasan, Sabiha B.; Hasan, Shahela B.; Hossain, Md. Sakhawat (Frontiers in Environmental Science, 2016)
Recently, recognition of negative environmental impacts associated with overuse of pesticides in the agricultural regions of Bangladesh has made it clear that unsustainable pest-control strategies must change. Integrated Pest Management (IPM) was developed for use as a tool in the production of healthy, sustainably grown food. A strategic approach to crop-pest control, IPM aims to minimize pest populations by combining environmentally friendly pest-control methods and economically viable farming practices. This study examined the impact of IPM on insect damage to crop-yield parameters in a rice agro-ecosystem. IPM methods tested were: 1) collection of egg masses; 2) sweeping (using a funnel shaped net to capture insects); 3) perching (installing a branch or pole which serves as a resting place for predatory birds); and 4) Economic Threshold Level (ETL) based insecticide application (The ETL is the point at which the value of the crop destroyed exceeds the cost of controlling the pest). We also examined the effects of prophylactic insecticide application and current management practices on rice yield. Rice-yield indicators included number of healthy tillers, number of hills, central leaf drying (Dead Heart), and grain-less panicles (White Head). For two consecutive years, the lowest percentages of Dead Heart (1.23 and 1.55) and White Head (2.06) were found in the IPM-treated plots. Further, the IPM-treated plots had higher yields (7.3-7.5 ton/ha) compared with the non-IPM treatments (6.28-7.02 ton/ha). The location of the plots appeared to be non-significant for all measured yield components. The effect of treatment on the percentage of Dead Heart, White Head, number of hills, and yield was statistically significant (p ≤ 0.05). We concluded that IPM is an effective strategy for obtaining high rice yields in sustainable rice agro-ecosystems.